Lost my home : React. - Erkstam, Filippa (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2024)
What happens in man when the society you live in disappear? Howis the individual affected when large external forces changes the life conditions? In northern Sweden, the societies Kiruna and Malmberget move due to the mining. The project started in Malmberget but soon got a wider perspective. Societies will continue to disappear which is already seen in Ukraine and parts of the world where climate change is a fact. Lost my home is an exploration in how emoticons and graphic design can be a help for people to communicate. Emoticons is built on feelings and is a language we all understand no matter which countries we are from. The project is the start of exploring how emoticons can be its own language and help us to move on.